Report of the Working Group on Horticulture Development (Fruits, Vegetables, Tuber Crops, Floriculture, Medicinal and Aromatic Plants, Spices, Plantation Crops including Tea, Coffee and Rubber) for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
Constitution of Working Group on Horticulture Development including Spices, Aromatic and Medicinal Plants and Plantation Crops for formulation of the Tenth Five year Plan (2002-2007). Constitution of Sub-Group on Fruits to assist the Working Group on Horticulture Development including Spices, Aromatic & Medicinal Plants and Plantation Crops for formulation of the Tenth Five Year Plan (2002-07)- Regarding.
Government of India Planning Commission
Government of India Planning Commission